Effectiveness of the Minder Mobile Mental Health and Substance Use Intervention for University Students: Randomized Controlled Trial - Melissa Vereschagin; Angel Y Wang; Chris G Richardson; Hui Xie; Richard J Munthali; Kristen L Hudec; Calista Leung; Katharine D Wojcik; Lonna Munro; Priyanka Halli; Ronald C Kessler; Daniel V Vigo (JMIR Publications, 2024)
BackgroundUniversity attendance represents a transition period for students that often coincides with the emergence of mental health and substance use challenges. Digital interventions have been identified as a promising means of supporting students due to their scalability, adaptability, and acceptability. Minder is a mental health and substance use mobile app that was codeveloped with university students. ObjectiveThis study aims to examine the effectiveness of the Minder mobile app in improving mental health and substance use outcomes in a general population of university students. MethodsA 2-arm, parallel-assignment, single-blinded, 30-day randomized controlled trial was used to evaluate Minder using intention-to-treat analysis. In total, 1489 participants were recruited and randomly assigned to the intervention (n=743, 49.9%) or waitlist control (n=746, 50.1%) condition. The Minder app delivers evidence-based content through an automated chatbot and connects participants with services and university social groups. Participants are also assigned a trained peer coach to support them. The primary outcomes were measured through in-app self-assessments and included changes in general anxiety symptomology, depressive symptomology, and alcohol consumption risk measured using the 7-item General Anxiety Disorder scale, 9-item Patient Health Questionnaire, and US Alcohol Use Disorders Identification Test-Consumption Scale, respectively, from baseline to 30-day follow-up. Secondary outcomes included measures related to changes in the frequency of substance use (cannabis, alcohol, opioids, and nonmedical stimulants) and mental well-being. Generalized linear mixed-effects models were used to examine each outcome. ResultsIn total, 79.3% (589/743) of participants in the intervention group and 83% (619/746) of participants in the control group completed the follow-up survey. The intervention group had significantly greater average reductions in anxiety symptoms measured using the 7-item General Anxiety Disorder scale (adjusted group mean difference=−0.85, 95% CI −1.27 to −0.42; P<.001; Cohen d=−0.17) and depressive symptoms measured using the 9-item Patient Health Questionnaire (adjusted group mean difference=−0.63, 95% CI −1.08 to −0.17; P=.007; Cohen d=−0.11). A reduction in the US Alcohol Use Disorders Identification Test-Consumption Scale score among intervention participants was also observed, but it was not significant (P=.23). Statistically significant differences in favor of the intervention group were found for mental well-being and reductions in the frequency of cannabis use and typical number of drinks consumed. A total of 77.1% (573/743) of participants in the intervention group accessed at least 1 app component during the study period. ConclusionsIn a general population sample of university students, the Minder app was effective in reducing symptoms of anxiety and depression, with provisional support for increasing mental well-being and reducing the frequency of cannabis and alcohol use. These findings highlight the potential ability of e-tools focused on prevention and early intervention to be integrated into existing university systems to support students' needs. Trial RegistrationClinicalTrials.gov NCT05606601; https://clinicaltrials.gov/ct2/show/NCT05606601 International Registered Report Identifier (IRRID)RR2-10.2196/49364